Research on transmission based on collaboration coding in WSNs - Xiao-Xing, L.V.; Bai-Hai, Z. (Journal of Digital Information Management, 2013)
In order to reduce the increase of network delay and excessive energy consumption, which are caused by network code in WSNs, a fast random linear mechanism of network coding based on nodes collaboration is introduced. Energy consumption of nodes is reduced by transmitting the initial code of the node, and transmitting linear independent packets received merely. After gathering node coding, ACK return along the best path to reduce the network delay. Simulation results show that delay of data transmission is reduced greatly by introducing random linear network coding for sensor network, and the improved coded mode balances the network load.
Keywords: Nodes Collaboration; Random Linear Network Coding; Wireless sensor network